Phase transition of individual anatase TiO2 microcrystals with large percentage of (001) facets: a Raman mapping and SEM study. Issue 4 (10th January 2023) - Lu, Weigang; Zhu, Hao; Birmingham, Blake; Craft, Nolan; Hu, Jonathan; Park, Kenneth; Zhang, Zhenrong
Abstract : The anatase–rutile phase transition of anatase microcrystals is dominated by surface nucleation and growth. The anatase/rutile co-existing particle will be a perfect platform to study the anatase/rutile synergistic effect in catalysis. Abstract : TiO2 has been extensively studied in many fields including photocatalysis, electrochemistry, optics, etc. Understanding the mechanism of the anatase–rutile phase transition (ART) process is critical for the design of TiO2 -based high-activity photocatalysts and tuning its properties for other applications. In this work, the ART process using individual anatase micro-particles with a large percentage of (001) facets was monitored and studied. Phase concentration evolution obtained via Raman microscopy was correlated with the morphological evolution observed in scanning electron microscope (SEM) images. The ART of anatase microcrystals is dominated by surface nucleation and growth, but the ART processes of individual anatase particles are distinctive and depend on the various rutile nucleation sites. Two types of transformation pathways are observed. In one type of ART pathway, the rutile phase nucleated at a corner of an anatase microcrystal and grew in one direction along the edge of the crystal firstly followed by propagation over the rest of the microcrystal in the orthogonal direction on the surface and to the bulk of the crystal. The kinetics of the ART follows the first-order model with two distinct rate constants. The fast reaction rate is from the surface nucleation and growth, and the slow rate is from the bulk nucleation and growth. In the other type of ART pathway, multiple rutile nucleation sites formed simultaneously on different edges and corners of the microcrystal. The rutile phase spread over the whole crystal from these nucleation sites with a small contribution of bulk nucleation. Our study on the ART of individual micro-sized crystals bridges the material gap between bulk crystals and nano-sized TiO2 particles. The anatase/rutile co-existing particle will provide a perfect platform to study the synergistic effect between the anatase phase and the rutile phase in their catalytic performances.